Anamnesis: A Term—or Rather a Concept?. (March 2020) - Weis, Marco
This is a statement for the Young Scholars' Panel at the Congress of Societas Liturgica 2019 in Durham, UK. The short reflection is based on the major presentations and the upcoming questions by the congress: what does "anamnesis" mean, how is it connected to emotional affects, how can we produce it, or should we just have to let it happen through God himself.